Route Planning Using Multicasting Approach in Vehicular Ad Hoc Networks - Kumar, Ritesh; Mishra, Yogesh Chandra; Chaurasiya, Vijay Kumar (Wireless personal communications, 2023)
It is essential to ensure the safety, comfort, mobility, and quality of enormous traffic commonly seen in smart cities every day. Intelligent transport systems (ITS) are introduced to provide such facilities. A Vehicular Ad-Hoc Network (VANET) is a network made up of multiple vehicular nodes that can freely join and exit the network. VANET is an important part of the ITS development process for all applications. Several researchers from all over the world have been drawn to this new research subject. VANETs are mainly used to make sure the protection of vehicles on the street and to enhance visitors’ performance and luxury for individuals. Due to the growing mobility of vehicles inside VANETs, it’s far tough to set up a safe and efficient route between the source and destination nodes. To choose the path between source and destination, this study analyses two factors: the least hop count and the sequence number. Firstly, the path is established using the multi-casting method in this research work. After that, the data is routed to select the root nodes from the network in the multi-casting method. Then the path is selected amid source and destination using a root node. The projected method is deployed on Network Simulator-2 (NS2), and the analytic outcomes are obtained to evaluate specific parametric values. The result shows that packet loss is reduced by 59.1% and delay is reduced by 18.2% when the multi-casting technique is used for establishing a path between source to destination as compared to the broadcasting method besides it throughput has also increased by 74% in the multi-casting domain compared to other existing methods.